Awliya’ ‘Inda Sayyid Quthb fi Tafsîr Zhilâl Al-Qur`an - Muhammad Irfanuddin (Universitas Darussalam Gontor, 2018)
This paper discusses about the term awliya` in Qur'an, which is one of the most popular discussion among the society, both in terms of meaning and tafseer. Sayyid Qutb is one of the most active mufasir in the field of movement and politics, so he focuses more on the study of term awliya’ in the Qur'an. Sayyid Qutb explains the word awliya’ has various meanings, depend on the context of the verse. First, it related to Jews, Christians and Gentiles, who show help, fellowship by realizing them as regulators of the Muslim way of life. Second, it related to Allah, who has the meaning of a helper, guide, protector, and who has all the power. The third relates to the believers, who explain the believers who are devoted to Allah and always call upon goodness and apostasy. Fourth, it related to Syaithan who makes him awliya', and indeed the awliya' referred to awliya’ for unbelievers.